2018
DOI: 10.1136/bmjopen-2017-019878
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the mixed-methods process and context evaluation of theTB & Tobaccorandomised controlled trial in Bangladesh and Pakistan: a hybrid effectiveness–implementation study

Abstract: IntroductionTuberculosis (TB) remains a significant public health problem in South Asia. Tobacco use increases the risks of TB infection and TB progression. The TB& Tobacco placebo-controlled randomised trial aims to (1) assess the effectiveness of the tobacco cessation medication cytisine versus placebo when combined with behavioural support and (2) implement tobacco cessation medication and behavioural support as part of general TB care in Bangladesh and Pakistan. This paper summarises the process and contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Different project work packages, such as a quantitative process evaluation component and the context evaluation, will help fill in potential gaps left by this interview study. 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different project work packages, such as a quantitative process evaluation component and the context evaluation, will help fill in potential gaps left by this interview study. 29…”
Section: Discussionmentioning
confidence: 99%
“…Details of the behaviour support intervention, the cytisine trial and the process evaluation are published in the process evaluation and the trial protocols. 11,29 In short, regarding the behaviour support intervention, we aimed to systematically assess the implementation process at clinic level and to discover mechanisms of interaction between participants and the intervention by observing and interviewing patients and health workers. For the qualitative process evaluation components, we chose a multi-site case study design 30,31 to gain an understanding of the multi-faceted and complex real-life contexts at the clinic level.…”
Section: Methodsmentioning
confidence: 99%
“…Since previous studies have shown smoking is associated with an increased risk of TB (Boeckmann et al, 2018;Perriot et al, 2018;Zhang et al, 2019), six questions were asked about patients' smoking behaviour. In general, most of the respondents were not smokers (n=300, 69.9%) but admitted that they quit smoking after being diagnosed with or infected by TB.…”
Section: Statistics and Resultsmentioning
confidence: 99%
“…We will disseminate results via conferences, scientific forums, and publications as well as via reports and workshops targeted towards stakeholders. In reporting this protocol and the results of the process evaluation, we followed the MRC framework and previous study protocols and process evaluations with comparable approaches [34,35]. In addition, the complex intervention is reported based on the Criteria for Reporting the Development and Evaluation of Complex Interventions (CReDECI 2) [36] (Additional file 1).…”
Section: Reportingmentioning
confidence: 99%